Experimental Research Concerning the Energy Performance Determination of a New Type of Rotating Working Machine - Constantin, Mihaela; Băran, Nicolae; Tănase, Beatrice; Donisan, Evelina (Review of Environment and Earth Sciences, 2016)
The paper presents a rotating machine that consists of two profiled rotors placed in a case. The machine was designed and built in the laboratories of the Politehnica University of Bucharest and it can circulate both liquids and gas. The driving power and the flow rate computation relations of the machine are exposed. An experimental stand was conceived, designed and built where the rotating machine was tested performing with an effective efficiency of 77%. This constructive solution can be used in energetic industry, in agriculture and petrochemical industry.